Semantic Systems. In the Era of Knowledge Graphs 16th International Conference on Semantic Systems, SEMANTiCS 2020, Amsterdam, The Netherlands, September 7-10, 2020, Proceedings - Blomqvist, Eva; Groth, Paul; de Boer, Victor; Pellegrini, Tassilo; Alam, Mehwish; Käfer, Tobias; Kieseberg, Peter; Kirrane, Sabrina; Meroño-Peñuela, Albert; Pandit, Harshvardhan J. (Information Systems and Applications, incl. Internet/Web, and HCI, 2020)
This open access book constitutes the refereed proceedings of the 17th International Conference on Semantic Systems, SEMANTiCS 2020, held in Amsterdam, The Netherlands, in September 2020.